Rationale of construction processes in the social configuration of habitat: Nueva Colonia, Turbo, Colombia - Cuervo Calle, Juan José; Salazar Hernández, Cesar Augusto; Sánchez Holguín, Victoria Eugenia; Lalinde Castrillón, Luis Felipe; Sañudo Vélez, Luis Guillermo (Frontiers in Built Environment, 2023)
The alliance between universities, the private sector, the State and local communities becomes a fundamental strategy to channel regional development processes. This approach that interprets SDG 17 has been applied in the research courses of the Architecture Faculty of Universidad Pontificia Bolivariana. In these courses, real problems in specific regions of the national territory serve as a starting point to contribute to the training of the architect from the perspective of social responsibility. Specifically, this text focuses on the Sustainable Environment research course, which took as a case study the corregimiento of Nueva Colonia (Turbo-Colombia) to propose technologies that reconfigure positively urban and rural areas. These technologies are proposed as a response to the social, cultural, and economic realities and the conditions that govern construction activity in the region. Based on participatory design as a working method, students design tools that allow collecting information about the perception that the community has of their territory with the purpose of determining basic design guidelines defined collaboratively to provide solutions to the habitat and the built environment. These guidelines derive mainly from a reflection on technology in the construction of social housing, socio-environmental relationships, and their repercussions for the sustainable configuration of the built environment. To achieve this goal, students research on ecoefficient materials and local waste that can be used as construction material or raw material, and 2 This is a provisional file, not the final typeset article which are preliminarily evaluated using circularity and life cycle criteria. In this sense, this text seeks to highlight specific results of eco-efficient materials and waste from the banana industry.